Question Number 193585 by York12 last updated on 16/Jun/23
$$ \\ $$$${There}\:{exists}\:{a}\:{unique}\:{positive}\:{integer}\:{a}\:{for} \\ $$$${which}\:{The}\:{sum}\:{u}\:\:=\:\underset{{n}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\lfloor\frac{{n}^{\mathrm{2}} −{na}}{\mathrm{5}}\rfloor\:{is}\:{an}\:{integer} \\ $$$${trictly}\:{between}\:−\mathrm{1000}\:\&\:\mathrm{1000}\:{find}\:{a}+{u}. \\ $$
Answered by York12 last updated on 16/Jun/23
$$ \\ $$$$ \\ $$$$\boldsymbol{{u}}=\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\lfloor\frac{\boldsymbol{{n}}^{\mathrm{2}} −\boldsymbol{{na}}}{\mathrm{5}}\rfloor\:,\:\lfloor\frac{\boldsymbol{{n}}^{\mathrm{2}} −\boldsymbol{{na}}}{\mathrm{5}}\rfloor=\frac{\boldsymbol{{n}}^{\mathrm{2}} −\boldsymbol{{na}}}{\mathrm{5}}−\left\{\frac{\boldsymbol{{n}}^{\mathrm{2}} −\boldsymbol{{na}}}{\mathrm{5}}\right\} \\ $$$$\boldsymbol{{where}}\:\left\{\circledast\right\}\:\boldsymbol{{indicates}}\:\boldsymbol{{the}}\:\boldsymbol{{fractional}}\: \\ $$$$\boldsymbol{{part}}\:\boldsymbol{{function}}\: \\ $$$$\mathrm{0}\leqslant\left\{\frac{\boldsymbol{{n}}^{\mathrm{2}} −\boldsymbol{{na}}}{\mathrm{5}}\right\}<\mathrm{1}\:\Rightarrow\:\mathrm{0}\leqslant\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\left\{\frac{\boldsymbol{{n}}^{\mathrm{2}} −\boldsymbol{{na}}}{\mathrm{5}}\right\}<\mathrm{2023} \\ $$$$−\mathrm{1000}<\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\lfloor\frac{\boldsymbol{{n}}^{\mathrm{2}} −\boldsymbol{{na}}}{\mathrm{5}}\rfloor<\mathrm{1000}\:\Rightarrow\:\mathrm{0}<\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\left(\frac{\boldsymbol{{n}}^{\mathrm{2}} −\boldsymbol{{na}}}{\mathrm{5}}\right)−\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\left\{\frac{\boldsymbol{{n}}^{\mathrm{2}} −\boldsymbol{{na}}}{\mathrm{5}}\right\}<\mathrm{1000} \\ $$$$\Rightarrow−\mathrm{3023}<\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\left(\frac{\boldsymbol{{n}}^{\mathrm{2}} −\boldsymbol{{na}}}{\mathrm{5}}\right)<\mathrm{1000} \\ $$$$\Rightarrow−\mathrm{3023}<\frac{\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\left(\boldsymbol{{n}}^{\mathrm{2}} \right)}{\mathrm{5}}−\frac{\boldsymbol{{a}}\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\left(\boldsymbol{{n}}\right)}{\mathrm{5}}<\mathrm{1000} \\ $$$$\Rightarrow\mathrm{5}×\left(\mathrm{3023}+\frac{\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\left(\boldsymbol{{n}}^{\mathrm{2}} \right)}{\mathrm{5}}\right)>\boldsymbol{{a}}>\mathrm{5}×\left(\frac{\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\left(\boldsymbol{{n}}\right)}{\mathrm{5}}−\mathrm{1000}\right) \\ $$$$\Rightarrow\:\mathrm{1349}.\mathrm{007}>{a}>\mathrm{1348}.\mathrm{998}\:\Rightarrow\:{a}=\mathrm{1349} \\ $$$$\therefore\boldsymbol{{u}}=\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\lfloor\frac{\boldsymbol{{n}}^{\mathrm{2}} −\mathrm{1349}\boldsymbol{{n}}}{\mathrm{5}}\rfloor=\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\left(\frac{\boldsymbol{{n}}^{\mathrm{2}} −\mathrm{1349}\boldsymbol{{n}}}{\mathrm{5}}\right)−\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\left\{\frac{\boldsymbol{{n}}^{\mathrm{2}} −\mathrm{1349}\boldsymbol{{n}}}{\mathrm{5}}\right\} \\ $$$$\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\left(\frac{\boldsymbol{{n}}^{\mathrm{2}} −\mathrm{1349}\boldsymbol{{n}}}{\mathrm{5}}\right)=\mathrm{0}\:\Rightarrow\:\boldsymbol{{u}}=−\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\left\{\frac{\boldsymbol{{n}}^{\mathrm{2}} −\mathrm{1349}\boldsymbol{{n}}}{\mathrm{5}}\right\} \\ $$$$\boldsymbol{{so}}\:\boldsymbol{{now}}\:\boldsymbol{{we}}\:\boldsymbol{{are}}\:\boldsymbol{{only}}\:\boldsymbol{{intrested}}\:\boldsymbol{{in}}\:\boldsymbol{{the}}\:\boldsymbol{{value}} \\ $$$$\boldsymbol{{of}}\:\boldsymbol{{the}}\:\boldsymbol{{Remainder}}\:\boldsymbol{{of}}\:\boldsymbol{{the}}\:\boldsymbol{{expression}} \\ $$$$\frac{\boldsymbol{{n}}^{\mathrm{2}} −\mathrm{1349}\boldsymbol{{n}}}{\mathrm{5}}\:\:,\:\boldsymbol{{one}}\:\boldsymbol{{of}}\:\boldsymbol{{the}}\:\boldsymbol{{special}}\:\boldsymbol{{properties}} \\ $$$$\boldsymbol{{of}}\:\boldsymbol{{mod}}\:\left(\mathrm{5}\right)\:\&\:\boldsymbol{{mod}}\:\left(\mathrm{10}\right)\:\boldsymbol{{that}}\: \\ $$$$\boldsymbol{{a}}_{\boldsymbol{{n}}} \boldsymbol{{a}}_{\boldsymbol{{n}}−\mathrm{1}} \boldsymbol{{a}}_{\boldsymbol{{n}}−\mathrm{2}} \boldsymbol{{a}}_{\boldsymbol{{n}}−\mathrm{2}} …\boldsymbol{{a}}_{\mathrm{1}} \boldsymbol{{a}}_{\mathrm{0}} \:\equiv\:\boldsymbol{{a}}_{\mathrm{0}} \:\boldsymbol{{mod}}\:\left(\mathrm{5}\right) \\ $$$$\boldsymbol{{a}}_{\boldsymbol{{n}}} \boldsymbol{{a}}_{\boldsymbol{{n}}−\mathrm{1}} \boldsymbol{{a}}_{\boldsymbol{{n}}−\mathrm{2}} \boldsymbol{{a}}_{\boldsymbol{{n}}−\mathrm{2}} …\boldsymbol{{a}}_{\mathrm{1}} \boldsymbol{{a}}_{\mathrm{0}} \:\equiv\:\boldsymbol{{a}}_{\mathrm{0}} \:\boldsymbol{{mod}}\left(\mathrm{10}\right) \\ $$$$\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}} {\sum}}\left\{\frac{\boldsymbol{{n}}^{\mathrm{2}} −\mathrm{1349}\boldsymbol{{n}}}{\mathrm{5}}\right\}=\lfloor\frac{\mathrm{2023}}{\mathrm{5}}\rfloor\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{5}} {\sum}}\left(\frac{\left(\frac{\boldsymbol{{n}}^{\mathrm{2}} −\mathrm{1349}\boldsymbol{{n}}}{\mathrm{5}}\right)\boldsymbol{{mod}}\left(\mathrm{5}\right)}{\mathrm{5}}\right)+\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}\:\boldsymbol{{mod}}\left(\mathrm{5}\right)} {\sum}}\left(\frac{\left(\frac{\boldsymbol{{n}}^{\mathrm{2}} −\mathrm{1349}\boldsymbol{{n}}}{\mathrm{5}}\right)\boldsymbol{{mod}}\left(\mathrm{5}\right)}{\mathrm{5}}\right) \\ $$$$\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{5}} {\sum}}\left(\frac{\left(\frac{\boldsymbol{{n}}^{\mathrm{2}} −\mathrm{1349}\boldsymbol{{n}}}{\mathrm{5}}\right)\boldsymbol{{mod}}\left(\mathrm{5}\right)}{\mathrm{5}}\right)=\mathrm{1}\:,\:\underset{\boldsymbol{{n}}=\mathrm{1}} {\overset{\mathrm{2023}\:\boldsymbol{{mod}}\left(\mathrm{5}\right)} {\sum}}\left(\frac{\left(\frac{\boldsymbol{{n}}^{\mathrm{2}} −\mathrm{1349}\boldsymbol{{n}}}{\mathrm{5}}\right)\boldsymbol{{mod}}\left(\mathrm{5}\right)}{\mathrm{5}}\right)=\mathrm{1} \\ $$$$\Rightarrow\boldsymbol{{u}}=\:−\mathrm{1}×\left(\left(\mathrm{404}×\mathrm{1}\right)+\mathrm{1}\right)=−\mathrm{405} \\ $$$$\Rightarrow\:\boldsymbol{{u}}\:+\boldsymbol{{a}}\:=\mathrm{944}\: \\ $$